The effect of locally delivered doxycycline as an adjunctive therapy to scaling and root planing in smokers - Hassan Al Hulami; Nadir Babay; Fatin Awartani; Sukumaran Anil (Elsevier, 2011)
Background: Locally delivered doxycycline is found to be effective in managing periodontitis as an adjunct to scaling and root planing. Aim: To evaluate the effect of locally delivered doxycycline (10%) with scaling and root planing in the periodontal treatment of smokers and to compare it with scaling and root planing alone. Methods: Twelve smokers with chronic periodontitis and a pocket depth (⩾5 mm) on posterior teeth that bleed on probing were selected. Patients were randomly assigned to scaling and root planing (SRP) or scaling and root planing followed by local application of doxycycline (SRP-D). Plaque, bleeding on probing, gingival recession, clinical attachment level (CAL), and probing depth (PD) were recorded at the baseline, 6 and 12 weeks. Results: Both groups showed a significant reduction in Plaque, Bleeding on Probing and pocket depth at 6th and 12th week from the baseline. A statistically significant gain of attachment was observed in both groups after treatment. Even though the doxycycline group showed slightly higher attachment gain it was not statistically significant compared to the control group. Conclusion: The observations of the study reveal that the additional benefit of topical application of doxycycline as an adjunct to scaling and root planing in smokers is not convincing. However, further clinical studies may be necessary to substantiate the present observations. Keywords: Doxycycline, Scaling and root planing, Adjunctive therapy, Periodontitis, Drug delivery, Ultrasonic, Smoking